A large primary leiomyoma of right ventricle in a 4-year-old child: case report - Liu, Yefu; Yuan, Dou (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiac leiomyomas are extremely rare cardiac anomalies. Among them, primary leiomyomas confined to heart are even rarer, which have been reported only in few cases. Once diagnosed, surgical resection is the most common choice for treatment.Case summaryA 4-year-old girl with heart murmur was diagnosed with a large spherical mass which was located in the right ventricle. The oval mass measured approximately 50 × 40 mm and caused obstruction of the right ventricular outflow tract. To relieve the obstruction, the large mass was resected in surgery. During the surgery a 45 × 40 × 35 mm oval structure with stiff elastic consistence was found being attached to the free wall of the right ventricle. No other abnormalities like regurgitation were detected. Histopathological examination of the resected mass indicated a benign leiomyoma. Postoperative recovery was uneventful.DiscussionAs a benign cardiac tumor, leiomyoma is exceptionally rare. The majority of cardiac leiomyomas are metastatic. Primary ones are few. Imaging and histologic examination can help to diagnose. After surgical resection, most patients can recover well.